2016
DOI: 10.1155/2016/3206845
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Alternative Extraoral Periapical Technique for Patients with Severe Gag Reflex

Abstract: Gag reflex is a physiologic mechanism that promotes contraction of the muscles of the tongue and pharyngeal walls. Different factors, including intraoral radiographic films and sensors, may trigger this reflex. Patients with severe gag reflex may not be able to tolerate the presence of intraoral radiographic films or sensors during root canal therapy (RCT). This factor may prevent an appropriate intraoral radiograph, which is important in RCT. Different approaches have been used to facilitate dental procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Extraoral imaging such as panoramic radiograph or cone-beam computed tomography should be used to avoid the gag reflex or cough that may ensue with intraoral imaging. [ 31 ] When intraoral imaging is mandated, sensors should be double barrier to prevent perforation and cross-contamination. Dentists should use a rubber dam to reduce splatter generation.…”
Section: Protocols For Effective Infection Controlmentioning
confidence: 99%
“…Extraoral imaging such as panoramic radiograph or cone-beam computed tomography should be used to avoid the gag reflex or cough that may ensue with intraoral imaging. [ 31 ] When intraoral imaging is mandated, sensors should be double barrier to prevent perforation and cross-contamination. Dentists should use a rubber dam to reduce splatter generation.…”
Section: Protocols For Effective Infection Controlmentioning
confidence: 99%
“…A panoramic radiograph or cone-beam computed tomography (CBCT) can also be used as an alternative examination. 8 In another recent review study, Nasiri and Wrbas stated that electronic apex locators, regardless of their generation, prove to be beneficial for patients suffering from gag reflex or those who cannot endure X-ray film or sensor. 9 Another challenge for clinicians in this pandemic is the cyclic vomiting syndrome (CVS); it was first recognized in pediatrics; however, it is now confirmed that adults can also suffer from CVS.…”
mentioning
confidence: 99%